2016
DOI: 10.1186/s12909-016-0749-3
|View full text |Cite
|
Sign up to set email alerts
|

Research interest and activity among medical students in Gothenburg, Sweden, a cross-sectional study

Abstract: BackgroundThe proportion of physicians undertaking doctoral studies is decreasing. Early recruitment of medical students could counteract this trend. This follow-up survey investigated research interest and activity among medical students at the Sahlgrenska Academy, Gothenburg, Sweden.MethodsA questionnaire was administered to all medical students at the Sahlgrenska Academy, as a follow-up to a 2006 survey. The Mann-Whitney U test was used for ordinal variables and the Fisher exact test for categorical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
5
24
1
1
Order By: Relevance
“…24 Subsequent deficiency in research knowledge and skills of physicians could have negative effects on educational, clinical research and health care, shortening the translation of bridging between basics and clinical work. 27 This fact was confirmed in current study as our findings demonstrated inadequate skill and knowledge of research of the faculty as a main personal barrier towards research (p-0.011). On the other hand, 37.1% (n=157/423) participants of Amin TT realizes faculty low research knowledge and skill reduces their involvement in scientific activities.…”
Section: Bar Chart Presenting Barriers Towards Research Work Among Pgsupporting
confidence: 83%
See 1 more Smart Citation
“…24 Subsequent deficiency in research knowledge and skills of physicians could have negative effects on educational, clinical research and health care, shortening the translation of bridging between basics and clinical work. 27 This fact was confirmed in current study as our findings demonstrated inadequate skill and knowledge of research of the faculty as a main personal barrier towards research (p-0.011). On the other hand, 37.1% (n=157/423) participants of Amin TT realizes faculty low research knowledge and skill reduces their involvement in scientific activities.…”
Section: Bar Chart Presenting Barriers Towards Research Work Among Pgsupporting
confidence: 83%
“…2,29 Attractive stipend/scholarship, review/reformation of curriculum and trained and easy availability of supervisor/mentor, enrollment early in research of medical students have been recommended that can boost interest of under/postgraduate medical and dental students in scientific activities and assists undergraduate medical students to engage in research during their graduation which would make them able to conduct research easily in their post-graduation. 27 Medical and electronic data availability assist in discovering knowledge gap thus helps PG trainees to initiate their research work. The students cited bounded approach to the relevant medical and other electronic databases made them difficult to initiate their research activities.…”
Section: Bar Chart Presenting Barriers Towards Research Work Among Pgmentioning
confidence: 99%
“…The overwhelming majority of female physicians cited their interest in research as the reason for entering into a career of Basic Sciences. Given that motivations to choose medicine as a career path include an outstanding aptitude in medical science, a substantial work ethic, and a fervent desire to improve community health [ 23 , 40 ], these outcomes are an expected result. Female doctors join the many young professionals with families to seek work-life balance.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by an increased awareness of the importance of involvement in research through the activities of student research units and the changes that occurred in the SCFHS criteria of admission into postgraduate programmes. It is worth noting that research involvement of both the 2015 and 2017 graduates is higher than other studies done in Sweden and Brazil 13,14. However, both of these studies were conducted on medical students, while our study was conducted on medical graduates, who had more time to be involved in research.…”
Section: Discussionmentioning
confidence: 74%